2007
DOI: 10.1128/jb.00429-07
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial CT441 Is a PDZ Domain-Containing Tail-Specific Protease That Interferes with the NF-κB Pathway of Immune Response

Abstract: Chlamydia species are bacterial pathogens that affect over 140 million individuals worldwide. Ocular infection by Chlamydia trachomatis is the leading cause of preventable blindness, and urogenital tract infection by Chlamydia causes sexually transmitted disease. As obligate intracellular organisms, Chlamydia species have evolved mechanisms to evade the host immune system, including the degradation of the transcription factors regulatory factor X5 and upstream stimulation factor 1, which are required for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 26 publications
0
70
0
Order By: Relevance
“…either in Gram-negative bacteria (where many have been shown to affect virulence) or in non-pathogenic Grampositive species (where one example is known to affect sporulation) (Bandara et al, 2008;Lad et al, 2007;Marasco et al, 1996;Ostberg et al, 2004;Pan et al, 2003). In this work we have, for the first time, to our knowledge, identified and characterized a C-terminal protease from a Grampositive, pathogenic bacterial species.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…either in Gram-negative bacteria (where many have been shown to affect virulence) or in non-pathogenic Grampositive species (where one example is known to affect sporulation) (Bandara et al, 2008;Lad et al, 2007;Marasco et al, 1996;Ostberg et al, 2004;Pan et al, 2003). In this work we have, for the first time, to our knowledge, identified and characterized a C-terminal protease from a Grampositive, pathogenic bacterial species.…”
Section: Discussionmentioning
confidence: 82%
“…Recent work by ourselves and others has shown that amino terminal peptidases and CTPs can play an important role in bacterial virulence (Bandara et al, 2008;Carroll et al, 2012Carroll et al, , 2013Lad et al, 2007;Wang et al, 2012). These findings, along with the observation that C-terminal processing peptidases are poorly understood in Gram-positive pathogens, led us to investigate the role of C-terminal processing peptidases in S. aureus.…”
Section: Identification Of Ctpa In S Aureusmentioning
confidence: 99%
See 2 more Smart Citations
“…CT441 is a chlamydial tail-specific protease (Tsp) with a catalytic serine and a PDZ domain. It has been reported to interfere with the pro-inflammatory NF-B signalling pathway of the host cell, modulating antimicrobial and inflammatory responses Lad, Yang et al, 2007). However, in subsequent reports, the role of CT441 in the cleavage of NF-B has been questioned (Chen et al, 2012;Christian et al, 2010).…”
Section: Introductionmentioning
confidence: 96%